Politics go to the movies international relations and politics in genre films and television - Campbell, Joel R. (Lexington Books, 2022)
"This examination of film genres discusses how various films in five genres reflect or comment on political themes and ideas. The author uses constructivist and feminist political theory to examine the development of the political discourse in these films, and considers new ways to conceptualize the relationship between film or television and politics"--